Transnasal endoscopic surgery of bilateral congenital choanal atresia : report of two cases - Raja Lope Ahmad, Raja Ahmad Al'konee; Kamarudin, Norie Azilah; Balwant Singh, Gendeh (Faculty of Medicine, International Islamic University Malaysia, 2005)
Congenital choanal atresia is the developmental failure of the posterior nasal cavity to communicate with the nasopharynx. In the obligate nasal breathing neonate, this is a well recognized cause of nasal obstruction although it is rarely encountered. The diagnosis can be strongly suspected clinically but needs to be confirmed with flexible nasopharyngolaryngoscope or CT scanning. Currently transnasal endoscopic surgical repair is well accepted as surgical treatment. The surgical management of choanal atresia are disscussed further in details.